2002
DOI: 10.1177/155005940203300104
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Related Electrophysiological Subtypes of Cocaine Dependence

Abstract: We previously described the existence of two quantitative EEG (QEEG) subtypes of cocaine dependent males, identified at baseline, displaying differential proneness to relapse. The current study expands the population to include females and enhances the measure set to include both QEEG and somatosensory EP (SEP) features. Fifty-seven cocaine dependent adults (16 F, 41 M) were evaluated 5-14 days after last cocaine use, while in residence at a drug-free therapeutic community. The median length of stay in treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 78 publications
(79 reference statements)
0
25
0
Order By: Relevance
“…This was replicated in subsequent studies with a larger number of participants (Alper, 1999;Alper, Chabot, Kim, Prichep, & John, 1990;Alper, Prichep, Kowalik, Rosenthal, & John, 1998;Costa & Bauer, 1997;Herning et al, 1985;Noldy, Santos, Politzer, Blair, & Carlen, 1994;Prichep, Alper, Kowalik, & Rosenthal, 1996;Prichep et al, 1999;Prichep et al, 2002;Roemer et al, 1995). Beside beta effects, studies have reported an increase in delta activity (Herning et al, 1985) and frontal alpha activity (Herning, Glover, Koeppl, et al, 1994), whereas others have reported an increase in alpha wave EEG associated with bursts of cocaine-induced euphoria (Lukas, 1991).…”
Section: Qeeg In Sudmentioning
confidence: 85%
See 3 more Smart Citations
“…This was replicated in subsequent studies with a larger number of participants (Alper, 1999;Alper, Chabot, Kim, Prichep, & John, 1990;Alper, Prichep, Kowalik, Rosenthal, & John, 1998;Costa & Bauer, 1997;Herning et al, 1985;Noldy, Santos, Politzer, Blair, & Carlen, 1994;Prichep, Alper, Kowalik, & Rosenthal, 1996;Prichep et al, 1999;Prichep et al, 2002;Roemer et al, 1995). Beside beta effects, studies have reported an increase in delta activity (Herning et al, 1985) and frontal alpha activity (Herning, Glover, Koeppl, et al, 1994), whereas others have reported an increase in alpha wave EEG associated with bursts of cocaine-induced euphoria (Lukas, 1991).…”
Section: Qeeg In Sudmentioning
confidence: 85%
“…These data demonstrate the involvement of the prefrontal cortex in the qEEG response to acute cocaine and indicate that slow wave qEEG, delta and theta activity are involved in the processes related to experiencing rewarding properties of cocaine. Prichep et al (1999) and Prichep et al (2002) extended the idea of relating baseline EEG activity to outcome in cocainedependent patients in treatment programs. Participants with cocaine dependence have persistent changes in brain function assessed with qEEG methods, present when evaluated at baseline, 5 to 14 days after last reported crack cocaine use, and persistent at 1-and 6-month follow-up evaluations (Alper, 1999;Alper et al, 1990;Alper et al, 1998;Prichep et al, 1996;Prichep et al, 2002;Venneman et al, 2006).…”
Section: Qeeg In Sudmentioning
confidence: 99%
See 2 more Smart Citations
“…EEG changes in beta and theta power are typical for withdrawal from cocaine. Cocaine abusers who are still taking drug often present excess amount of both low-and high-frequency EEG activity (Prichep et al, 2002). Thus cocaine users may benefit from EEG biofeedback protocol aimed on increasing sensorimotor response (SMR) (12-15 Hz) and decreasing theta (4-8 Hz) activity at the vertex that is commonly used in the treatment of attention deficit 84 JOURNAL OF NEUROTHERAPY hyperactivity disorder (Monastra et al, 2005).…”
Section: Introductionmentioning
confidence: 99%